2022
DOI: 10.1186/s13020-022-00685-6
|View full text |Cite
|
Sign up to set email alerts
|

Integrated metabolomics, network pharmacology and biological verification to reveal the mechanisms of Nauclea officinalis treatment of LPS-induced acute lung injury

Abstract: Background Acute lung injury (ALI) is a severe inflammatory disease, underscoring the urgent need for novel treatments. Nauclea officinalis Pierre ex Pitard (Danmu in Chinese, DM) is effective in treating inflammatory respiratory diseases. However, there is still no evidence of its protective effect against ALI. Methods Metabolomics was applied to identify the potential biomarkers and pathways in ALI treated with DM. Further, network pharmacology w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 62 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…T-tests were performed to determine if there were significant differences in the relative peak areas of biomarkers between groups, selecting metabolites with statistical significance ( P < 0.05). The Human Metabolome Database (HMDB, http://www.hmdb.ca/ ) was utilized to identify potential markers [ 22 ]. Finally, differential metabolites were analysed for metabolic pathway enrichment using MetaboAnalyst 5.0 ( http://www.metaboanalyst.ca/ ) [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…T-tests were performed to determine if there were significant differences in the relative peak areas of biomarkers between groups, selecting metabolites with statistical significance ( P < 0.05). The Human Metabolome Database (HMDB, http://www.hmdb.ca/ ) was utilized to identify potential markers [ 22 ]. Finally, differential metabolites were analysed for metabolic pathway enrichment using MetaboAnalyst 5.0 ( http://www.metaboanalyst.ca/ ) [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Besides, several studies have shown that the activation of the PI3K/AKT pathway increases inflammatory cytokines by activating the downstream NF-κB signal [109][110][111]. However, some recent studies have drawn a different conclusion, suggesting that the activation of PI3K/AKT is related with the alleviation of lung inflammation [112,113]. Zhong et al [113] reported that PI3K/AKT activation inhibited downstream NF-κB and NLRP3 inflammasome to alleviate inflammation in LPS-induced ALI model.…”
Section: Pi3k/akt Signaling Pathwaymentioning
confidence: 99%